Replacing sea mud with attachment of suspension cage can improve growth and gut health for sea cucumber Apostichopus japonicus - Guo, Zhixu; Meng, Xiangyu; Zhang, Yuntian; Wu, Di; Zhang, Rongwei; Zhao, Xiaoran; Ren, Tongjun; Han, Yuzhe (Frontiers in Marine Science, 2024)
During the suspension cage culture procedure, a substantial quantity of attachments from the suspension cage will amass in the tidal flats, resulting in environmental pollution and resource wastage. The aim of the present study was to explore the feasibility of using attachments of suspension cage (ASC) as a raw feed material for sea cucumbers. Different ASC concentrations (0, 25, 50, 75, and 100%) were used in sea cucumber (Apostichopus japonicus) fed for 60 d. Replacing sea mud with 50% ASC significantly improved sea cucumber growth, reduced the feed coefficient, significantly increased the activity of intestinal digestive enzymes, improved the activities of acid phosphatase and alkaline phosphatase, improved the intestinal structure, and enriched intestinal microbiome diversity (P<0.05). Replacing sea mud with 75% and 100% ASC significantly improved sea cucumber total antioxidant capacity and total superoxide dismutase (P<0.05).Furthermore, expressions of c-myc gene, mapk-7 gene and fgfr-1 gene, which all three growth genes, significantly increased in the 50% ASC treatment compared to that in the control; whereas, that of gdf-8 gene, a negative growth regulator, was inhibited (P<0.05). Based on the quadratic regression analysis for the weight gain rate, the appropriate levels of ASC substitution were estimated as to be 44.28%. The results suggested the potential of ASC as a new raw feed material for sea cucumbers.